In Vivo Roles of Conjugation with Glutathione and O(6)-Alkylguanine DNA-Alkyltransferase in the Mutagenicity of the bis-Electrophiles 1,2-Dibromoethane and 1,2,3,4-Diepoxybutane in Mice - Cho, Sung-Hee (2013)
[Image: see text] Several studies with bacteria and in vitro mammalian systems have provided evidence for the roles of two thiol-based conjugation systems, glutathione (GSH) transferase and O(6)-alkylguanine DNA-alkyltransferase (AGT), in the bioactivation of the bis-electrophiles 1,2-dibromoethane and 1,2,3,4-diepoxybutane (DEB), the latter an oxidation product of 1,3-butadiene. The in vivo relevance of these conjugation reactions to biological activity in mammals has not been addressed, particularly with DEB. In the present work we used transgenic Big Blue® mice, utilizing the cII gene, to examine the effects of manipulation of conjugation pathways on liver mutations arising from dibromoethane and DEB in vivo. Treatment of the mice with butathionine sulfoxime (BSO) prior to dibromoethane lowered hepatic GSH levels, dibromoethane-GSH DNA adducts (N(7)-guanyl), and cII mutation frequency. Administration of O(6)-benzylguanine (O(6)-BzGua), an inhibitor of AGT, did not change the mutation frequency. Depletion of GSH (BSO) and AGT (O(6)-BzGua) both lowered the mutation frequency induced by DEB, and BSO lowered the levels of GSH-DEB N(7)-guanyl and N(6)-adenyl DNA adducts. Our results provide evidence that the GSH conjugation pathway is a major in vivo factor in dibromoethane genotoxicity; both GSH and AGT conjugation are major factors in the genotoxicity of DEB. The latter findings are considered to be of relevance to the carcinogenicity of 1,3-butadiene.